2006
DOI: 10.1002/hipo.20161
|View full text |Cite
|
Sign up to set email alerts
|

Opiates, psychostimulants, and adult hippocampal neurogenesis: Insights for addiction and stem cell biology

Abstract: Once thought to produce global, nonspecific brain injury, drugs of abuse are now known to produce selective neuro-adaptations in particular brain regions. These neuro-adaptations are being closely examined for clues to the development, maintenance, and treatment of addiction. The hippocampus is an area of particular interest, as it is central to many aspects of the addictive process, including relapse to drug taking. A recently appreciated hippocampal neuro-adaptation produced by drugs as diverse as opiates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 204 publications
(224 reference statements)
3
108
0
2
Order By: Relevance
“…Besides being toxic to neurons, drugs of abuse have been also shown to induce a decrease in hippocampal neurogenesis (reviewed by Eisch and Harburg, 2006), compromising the capacity of the brain to generate new neurons. In the adult mammalian brain there are two main neurogenic regions, the subventricular zone (SVZ) and the subgranular zone (SGZ) of the dentate gyrus in the hippocampus (reviewed by Gage, 2002).…”
Section: Inhibition Of Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Besides being toxic to neurons, drugs of abuse have been also shown to induce a decrease in hippocampal neurogenesis (reviewed by Eisch and Harburg, 2006), compromising the capacity of the brain to generate new neurons. In the adult mammalian brain there are two main neurogenic regions, the subventricular zone (SVZ) and the subgranular zone (SGZ) of the dentate gyrus in the hippocampus (reviewed by Gage, 2002).…”
Section: Inhibition Of Neurogenesismentioning
confidence: 99%
“…Cocaine (Yamaguchi et al, 2004;Mackowiak al., 2005) and methamphetamine (Teuchert-Noodt et al, 2000) were also reported to decrease hippocampal neurogenesis. Repeated or chronic exposure seems to be required to observe the inhibition in adult hippocampal neurogenesis induced by opiates or psychostimulants (Eisch and Harburg, 2006).…”
Section: Inhibition Of Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The particular effects seen for each receptor type are contextual and differ among cell types and at different stages of development. Immature neurons Eisch and Harburg, 2006;Narita et al, 2006a), astrocytes (Stiene-Martin and Hauser, 1990;Eriksson et al, 1990;Eriksson et al, 1991;Stiene-Martin and Hauser, 1991;Hauser et al, 1996;Stiene-Martin et al, 1998;Belcheva et al, 2005), oligodendrocytes (Knapp et al, 1998;Stiene-Martin et al, 2001), and their precursors (Persson et al, 2003a;Persson et al, 2003b;Persson et al, 2006;Kim et al, 2006) can respond uniquely to opioids. For example, MOR receptor activation can inhibit proliferation in immature astroglia, while activation of the same receptor type in immature oligodendroglia increases proliferation (Knapp et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Lesion of the DG blocks cocaine-induced conditioned place preference (CPP) (Meyers et al 2006;Hernandez-Rabaza et al 2008). Moreover, the DG is one of the few regions in the adult brain where neurogenesis continues to take place (Christie and Cameron 2006;Aimons et al 2010) and neurogenesis is thought to play an important role in the formation of addictive memory (Eisch and Harburg 2006;Canales 2007Canales , 2010Noona et al 2010). Finally, the DG is a brain region that is highly sensitive to nicotine and significantly affects synaptic plasticity.…”
mentioning
confidence: 99%